The impact of total neo-adjuvant treatment on nonoperative management in patients with locally advanced rectal cancer: The evaluation of 66 cases. Issue 3 (March 2020) - Asoglu, Oktar; Tokmak, Handan; Bakir, Baris; Demir, Gokhan; Ozyar, Enis; Atalar, Banu; Goksel, Suha; Koza, Burak; Guven Mert, Aslihan; Demir, Atakan; Guven, Koray
Abstract: Background: The study aimed to assess if adherence to a total-neoadjuvant-treatment (TNT) protocol followed by observation(watch-and-wait) led to the successful nonoperative-management of low-rectal-cancer. Methods: In this study, patients with primary, resectable-T3-T4, N0–N1 distal-rectal-adenocarcinoma underwent-chemoradiotherapy + consolidation-chemotherapy (TNT). During the-TNT-period, endoscopy, MRI, and FDG-PET/CT were performed. We allocated patients with complete-clinical-tumor-regression, who underwent endoscopy every two months, MRI every-four-months, and PET/CT every-six-months-after-treatment, to the observation-group(OG). All other patients were referred for surgery. The OG was followed-up. The primary endpoint was local tumor-ecurrence after allocation to the OG. Results: Between 2015 and 2018, we enrolled 66-patients. Of 60-patients who were eligible to participate, 39 had complete-clinical-response(cCR) and were allocated to the OG, six underwent local-excision (LE), and 15 underwent total-mesorectal-excision (TME). The median follow-up duration was 22 (9–42) months. The local-recurrence-rate in the OG was 15.3%, and the LE and TME rates were 16.6% and 0%, respectively. All recurrence cases were salvaged through either LE or TME. The-distant-metastasis rate was 5.1%, 16.6%, and 12.5% in the OG, LE, and TME groups, respectively. The endoscopic negative-predictive-value(NPV) was 50%, and the positive-predictive-value(PPV) was 76.9% in the surgery group (LE + TME). MRI; NPV-50%, PPV-76.9%. PET/CT; NPV-100%, PPV-93.3%. Six patients(28.57%) from surgery group achieved complete pathological response (cPR). Conclusion: Our results indicated a high proportion of selected-rectal-cancers with-cCR after neo-adjuvant-therapy could potentially be managed non-operatively, and major surgery may be avoided.